Ubezpieczenie upraw - Łozowski, Mieczysław (Insurance of Cultivatio, 2006)
Change of rules of insurance's protection from legal to voluntary caused considerable fall of number of agricultural insurances. After 1990 a great number of farmer's resignations were observed from the insurances, which became voluntary. Farmers were not prepared to a situation in which they had suddenly to take care of insurance protection on their own. Insurance protection comprises only about 5% of cultivation and about 10% of stock of animals. 7th July of 2005 the parliament enacted law about extra charges to insurances of agricultural tillages and farm animals, which creates legal basis for applying extra charges from budget resources to premium paid by farmers within insurance from risk of unforeseen events of loss in animal and vegetable production. The basic purpose of the act is a natural drop of costs of cultivation but through extra charges for policies there is a real chance to limitate various kinds of help. This system has to replace hitherto applied help of government for farmers in case of natural disasters. In the last years extra charges to natural disasters credit and tax reductions from the budget amounted on average to 280 million Polish zlotys per year. It has been estimated that about 15% of farm workers will use that new solution.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 54-59